Testing the impact of two afterschool museum outreach interventions on elementary children’s STEM outcomes: hands-on STEM alone or with STEM stories - Zucker, Tricia A.; Mesa, Michael P.; Bambha, Valerie P.; DeMaster, Dana M.; Ahmed, Yusra; Master, Allison; Hammond, Jason; McCallum, Cheryl (Frontiers in Education, 2025)
IntroductionThis randomized control trial (RCT) evaluated an afterschool program with 24 weeks of hands-on science, technology, engineering and math (STEM) activities that were developed and delivered by museum educators at sites where the majority of students experienced poverty. The program also encouraged parent involvement in STEM-related activities.MethodsWe contrasted two treatment approaches to understand conditions that best support informal STEM learning during the elementary school period of kindergarten to Grade 5 (K-5). Specifically, this included a 60-min weekly “Basic” program, as well as an enhanced “Stories” version with an additional 15-min read-aloud featuring women and girls doing STEM activities. We randomized 36 afterschool sites with 541 children to determine the benefits of the basic afterschool program and the added benefits of the stories on STEM attitudes, aspects of science achievement, and other outcomes.ResultsThere were improvements or interaction effects in three of the five measured child outcomes: STEM value, career aspirations, and perceived math abilities. The most notable finding was that children’s STEM value increased significantly in the Basic treatment (effect size, g = 0.25, p = 0.027) and trended positively in the Stories condition (g = 0.18, p = 0.66), relative to the control group. Parent involvement in STEM also showed some changes.DiscussionThese findings underscore the potential for informal, hands-on experiences to positively influence children’s STEM-related attitudes. However, findings also suggest that interventions may need to be more intensive or sustained across the late elementary grades to achieve more substantial impact.